Geomorphological Observations and Physical Hypotheses About Martian Dune Gullies - Adriano Nardi; Antonio Piersanti (Geosciences)
We propose the hypothesis that dune gullies and seasonal “meteorological” appearances observed on the same dunes (e.g., frosting) may have a common origin. These gullies are difficult to explain through the action of liquid flow. The occurrence of a spring flowing from the crest of a dune seems impossible to explain. However, these phenomena could originate from the impact of wind on the profiles of some large Martian dunes. This aerodynamic effect could seasonally generate all the meteorological phenomena we observe on these dunes (bodies of ice, frost, moisture trails, and vapor clouds) and as a result, produce gullies with a peculiar morphology different from the standard. Thus, dune gullies could originate from meteorological liquids, but through a process unlike those known on Earth. Evidence from the Kaiser, Russell, and Korolev Craters supports the possibility of a partial water cycle (a half-cycle), potentially the remnant of a complete ancient cycle.